2017
DOI: 10.12927/hcpol.2017.25101
|View full text |Cite
|
Sign up to set email alerts
|

What Do We Know and Not Know about the Professional Integration of International Medical Graduates (IMGs) in Canada?

Abstract: Background:The literature on international medical graduates (IMGs) in Canada is growing, but there is a lack of systematic analysis of the literature.Objectives:To examine (1) the major themes in academic and grey literature pertaining to professional integration of IMGs in Canada; and (2) the gaps in our knowledge on integration of IMGs.Methods:This paper is based on the scoping review of academic and grey literature published during 2001–2013 about IMGs in Canada.Results:The literature on IMGs focuses on (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 27 publications
6
25
0
1
Order By: Relevance
“…In many cases, this is the same licensing exam used for peers educated within the country. [1][2][3][4][5] However, the pass rate of MPs is usually lower. This delays their licensing, which has negative effects on both MPs and on the new country in need of physicians.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In many cases, this is the same licensing exam used for peers educated within the country. [1][2][3][4][5] However, the pass rate of MPs is usually lower. This delays their licensing, which has negative effects on both MPs and on the new country in need of physicians.…”
Section: Introductionmentioning
confidence: 99%
“…Studies from Australia, Canada, the UK, the USA and Sweden have shown a considerably lower success rate on exams for MPs than for nationally trained physicians. [1][2][3][4][5][6] These exams include those mandated before receiving a medical licence and those required for specialist/postgraduate training. 1-3 7 8 In Sweden, over 30% of MPs with a medical degree from outside the European Union/European Economic Area (EU/EEA) fail to pass the licensing examination on the first attempt, while the corresponding figure for nationally trained physicians is approximately 3%.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Limited studies conducted in the United States have begun to assess the integration of IMGs into US medical practices (Laird, L.D., Abu-Ras, W., and Senzai, F., 2013;. A larger body of research on IMGs practicing outside of the United States have assessed, and programs have attempted to address, integration of IMG physicians in Canada, Australia, and Sweden among others (Neiterman, E., Bourgeault, I.L., and Covell, C.L., 2017;McGrath, P., Henderson, D., Phillips, E., 2009;Neiterman, E., Salmonsson, L., and Bourgeault, I., 2015). In general, these studies focus on both the initial "fit" of the physician and the experience during the first few years of practice, recognizing integration can be difficult and needs to be explicitly addressed in order to promote retention.…”
Section: Discussionmentioning
confidence: 99%